Tiina Vahanen, FAO, talking REDD+ and local stakeholder engagement - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Tiina Vahanen, REDD Coordinator at the Food and Agriculture Organization (FAO), talked at Forest Day 6 on 2 December, 2012 on Governance frameworks for REDD+, creating a framework for REDD+. Forest Day is held on the side lines of COP18 promoting a sustainable landscape for people.